(untitled) (Research, Society and Development, 2021)
The ball mill is an important fragmentation equipment that is present in everyday life and in various areas from food to mineral. The objective of this work is to present practices on how to handle and maintain a ball mill on a laboratory scale, present an experimental practice model for determining the work index in ores and finally ways to adapt the product obtained from grinding to two models of particle size distribution based on an experiment performed on the study equipment. The guidelines for the use of the equipment and the experimental procedure are consistent with the literature and easy execution, the results of the particle size models are comparable with the GGS model being the one that best represent the particle size product obtained.